Conservation of maleo bird (Macrocephalon maleo) through egg hatching modification and ex situ management - YOHAN RUSIYANTONO; MOBIUS TANARI; MUHAMAD ILYAS MUMU (Biodiversitas Journal of Biological Diversity, 2011)
Rusiyantono Y, Tanari M, Mumu MI (2011) Conservation of maleo bird (Macrocephalon maleo) through egg hatching modification and ex situ management. Biodiversitas 12: 171-176. Over exploitation of maleo bird eggs has become the main problem. In addition, habitat demolition and fragmentation have also caused decrease in maleo bird population. This research aimed to know the effectiveness ofhatching pattern to produce maleo breeding, studying breeding pattern of maleo bird through hatching approaches of feed quality and temperature adjustment, and studying maleo bird respond towards caring pattern adjustment by measuring plasticity value. There were two phases in this research. The first phase was hatching by using modified incubator. The other one was the caring of the breeding from the result of hatching through feed pattern management using protein and energy balancing. The results of the research indicated that thehatching success was 65%; however, life endurance of the birds from birth to one month of age was only 40%. Their growth showed sufficiently high increase after passing critical period in their body-weight based on feeding pattern containing 21% of protein that was 64.93 g and 62.59 g for maleo in Lore Lindu National Park (LLNP) and Bangkiriang Wildlife Reserve (BWR), respectively. Their monthly body-weight increase was 33.06 g in average of feeding pattern containing 13% of protein for LLNP maleo birds and 36.99 g for the maleo in BWR. It was found that feeding pattern containing higher content of protein (21%) promoted significant increase in the body-weight of maleo birds. Feeding such birds with high protein content feed along with sufficient energy triggered their growth speed. Based on the findings, it was concluded that maleo birds could be preserved by way of hatching, while the birds could be fed with feedcontaining high protein and energy in order to accelerate their growth after hatching.